Using Edublogs to Enhance EFL Writing Unity and Structure Skills among Faculty of Education Students - Abdel-Haq, Eman Mohammed; Alshamy, Ansaam Mohamed Abdelaziz; Abed, Magdy Mohamed Amin (جامعة بنها - كلية التربية, 2020)
يهدف هذا البحث إلى تعزيز مهارتي التركيب والتماسك في الكتابة باللغة الإنجليزية كلغة أجنبية لدى طلاب الفرقة الثالثة شعبة اللغة الإنجليزية بكلية التربية جامعة بنها وذلك باستخدام المدونات التعليمية. ولقد تم استخدام التصميم التجريبي ذو المجموعة الواحدة (قياس قبلي بعدي) ولقد بلغت عينة الدراسة واحد وثلاثون طالب من طلاب الفرقة الثالثة شعبة اللغة الإنجليزية وتم تصميم قائمة بالمهارات اللازمة لهؤلاء الطلاب لمعرفة مدى توافر هذه المهارات لديهم؛ كما تم تحكيمها بواسطة عدد من المحكمين الخبراء في مجال المناهج وطرق تدريس اللغة الإنجليزية. وتم تصميم اختبار قبلي بعدي لقياس مهارتي التركيب والتماسك لدى العينة. تم اختبار الطلاب قبليا لتحديد مستوى أدائهم القبلي وتدريبهم خلال استخدام المدونات التعليمية على كيفية تنمية وتعزيز مهارتي التركيب والتماسك في الكتابة. ولقد تم إعادة تطبيق الاختبار على الطلاب لقياس مدى التقدم في مستوى أدائهم ولقد أثبتت النتائج عن وجود فرق في أداء الطلاب قبل وبعد تطبيق الاختبار وذلك لصالح الاختبار البعدي مما يدل على مدى فاعلية استخدام المدونات التعليمية لتعزيز وتنمية مهارات التركيب والتماسك في الكتابة باللغة الإنجليزية.
The aim of the present study was to enhance EFL writing unity and structure skills among third year Student- Faculty of Education- Benha University through using the edublogs. The participants of the study consisted of third year English section students enrolled in Faculty of Education, Benha University (N=31). The study followed the one-group pre-posttest design. In addition, it used quantitative method for collecting and analyzing the data. The instruments of the present study were: an EFL writing skills checklist, an EFL writing test and a rubric to score it. Using the edublogs was applied to the participants during the first semester of the academic year 2017/2018. Results of the quantitative analysis revealed that the participants' EFL writing unity and structure skills were improved significantly as a result of using edublogs. Therefore, it can be concluded that that using edublogs is effective in improving the EFL writing unity and structure skills among prospective teachers of English.
Keywords: مهارات الكتابة -- اللغة الإنجليزية -- المدونات التعليمية -- طلبة الجامعات -- جامعة بنها